Optimization of thermal transfer in rotor-stator systems with multiple jets: impact on energy efficiency - Abdellatif EL hannaoui; Chadia Haidar; Rachid Boutarfa (Ain Shams Engineering Journal, 2025)
This study presents an integrated numerical and experimental investigation of convective heat transfer in a rotor–stator system subjected to multiple impinging air jets a configuration commonly used in the cooling of rotating machinery. The methodology combines computational fluid dynamics (CFD) using ANSYS Fluent with the Reynolds Stress Model (RSM) for turbulence modeling, selected for its capability to capture anisotropic and rotation-driven turbulent structures. The computational domain is discretized with a refined tetrahedral mesh, and simulations are validated against experimental data obtained through infrared thermography and thermocouple measurements. This combined approach ensures both physical fidelity and computational accuracy in evaluating flow and heat transfer behavior. The analysis focuses on three dimensionless parameters: the jet Reynolds number (Rej), varying from 1.6×104 to 5.4×104; the rotational Reynolds number (Reω), ranging from 2.32×105 to 5.4×105; and the dimensionless gap ratio (G = e/R), between 0.02 and 0.16. The local Nusselt number (Nur) is analyzed as a function of normalized radial position (r/D). Results reveal that increasing both Rej and Reω enhances convective heat transfer, with distinct thermal behaviors observed across the disk: weak transfer near the center, intensified interaction in intermediate regions, and thermal gradient amplification at the periphery due to recirculation. Correlations are established for the maximum Nusselt number (Numax) and average Nusselt numbers, revealing nonlinear dependencies on Rej, Reω, and G. These findings contribute valuable design guidelines for improving cooling efficiency in rotating systems such as wind turbines, high-speed electric motors, and generators, where thermal performance is critical for reliability and energy efficiency.